The effect of case-based mobile virtual patient application on students’ academic achievement in clinical reasoning skills - Levent Çetinkaya; İ̇lke Keser; Serkan Yildirim; Hafize Keser (Medical Education Online, 2024)
This mixed-method study aims to determine the effect of the use of mobile virtual patient application with narrated case-based virtual patients as an assistive technology on students’ clinical reasoning skills. It makes a notable contribution by exploring the impact of mobile virtual patient applications on healthcare students’ clinical skills and their preparation for real-world patient care. In addition, the accuracy of the analysis results regarding the effect on student achievement was analyzed with a second dataset tool, and thus, aiming to increase reliability by verifying the same research question with a different quantitative analysis technique. In the qualitative part of the study, students’ views on the implementation were collected through an open-ended questionnaire and the data were subjected to content analysis. An achievement test was also developed to determine the development of students’ clinical reasoning skills, which revealed that each of the learning environments had different outcomes regarding students’ achievement and that supporting the traditional environment with the mobile virtual patient application yielded better results for increasing students’ achievement. Students’ opinions about the mobile virtual patient application and the process also support the increase in academic achievement aimed at measuring clinical reasoning skills. The content analysis showed that the students, who generally reported multiple positive factors related to the application, thought that the stories and cases presented created a perception of reality, and they especially highlighted the contribution of the application to learning the story organization. Based on all these results, it can be said that the application supports clinical reasoning, provides practical experience, improves academic achievement, and contributes positively to motivation.